A critical discourse analysis of President Trump’s Speech to the Arab Islamic American Summit on May,21st, 2017 - Nguyễn, Thị Thu Khánh (2020)
In my study, I employ Fairclough’s theoretical framework and Halliday’s Systemic Functional Grammar to analyze a case study which is a political speech named “President Trump’s Speech to the Arab Islamic American Summit”. The study aims at deciphering the relationship between language, ideologies and power behind the discourse. To fulfill above mentioned purposes, the linguistic strategies are analyzed to see how the ideologies of speech are constructed. The result after analyzing this discourse draws out the major findings that language is not only shaped by the society around it, but an effective tool to convey ideas and at the same time affects the thinking of the hearers and the society. Language constructs one’s themes or ideologies. By analyzing this case study, it can be seen that Trump has flexibly used his linguistic strategies to get his opinions across and persuade the audience to action according to his policies.